Psychological type and personal wellbeing among Catholic priests in Italy: a study in positive psychology - Crea, Giuseppe (Mental health, religion & culture, 2021)
This paper explores the connection between psychological type and personal wellbeing among a sample of 95 Catholic priests serving in Italy. Personal wellbeing was assessed by two measures: the Oxford Happiness Questionnaire and the Purpose in Life Scale. Psychological type was assessed by the Francis Psychological Type Scales that draw on the development of Jung’s classic model that distinguishes between two orientations (extraversion and introversion), two perceiving functions (sensing and intuition), two judging functions (thinking and feeling), and two attitudes (judging and perceiving). The data demonstrated that lower levels of personal wellbeing were experienced by introverts than by extraverts.